Environmental Sanitation and Incidence of Stunting in Children Aged 12-59 Months in Ogan Ilir Regency - Imelda Gernauli Purba; Elvi Sunarsih; Inoy Trisnaini; Rico Januar Sitorus (Universitas Airlangga, 2020)
Introduction: Ogan Ilir is one of the three regency with the highest stunting incidence in South Sumatera. Environment factor is indirect causes of stunting in toddlers. The objective of this study therefore was to analyze the correlation between environmental sanitation with the incidence of stunting on toddler in Ogan Ilir Regency. Method: An observational analytical with a Cross sectional approach was conducted to determine incidence of stunting and associated environmental sanitation factors among toddler. Samples were toddler aged 12-59 months around 152 which selested by Multi Stage Cluster Sampling. Data was collected through interviews using questionnaries and observation was using checklist. The data was analyzed using Analysis of covariance test at (α=0.05). Result and Discussion: There was significant association between physical quality of clean water with incidence of stunting (p=0.036). Also, quqlity of sewerage significantly correlated to incidence of stunting (p=0.011). Significantly association also found between quality of latrines with incidence of stunting (p=0.005). On the other hand, history of infectious disease (p=0.100), personal hygiene (p=0.347), pesticide exposure (p=0.06), and cigarette smoke exposure (p=0.077) were not associated with inciden of stunting. Conclusion:Indirectly, the incidence of toddlers stunting is determined by environmental sanitation.